tim x : b, (2x-1)+(x+3)mũ 2 – 5(x-7 ) . ( x+7 ) = 0 anh chi giup e nhanh voi ak em dg can gap :’)

tim x :
b, (2x-1)+(x+3)mũ 2 – 5(x-7 ) . ( x+7 ) = 0
anh chi giup e nhanh voi ak em dg can gap :’)

0 bình luận về “tim x : b, (2x-1)+(x+3)mũ 2 – 5(x-7 ) . ( x+7 ) = 0 anh chi giup e nhanh voi ak em dg can gap :’)”

  1. $(2x -1) + (x+3)^2 – 5(x – 7)(x+7) = 0$

    $\Leftrightarrow 2x – 1 + x^2 + 6x + 9 – 5(x^2 – 49) = 0$

    $\Leftrightarrow -4x^2 + 8x +253 = 0$

    $\Leftrightarrow \left[\begin{array}{l} x =\dfrac{2 – \sqrt{257}}{2}\\x = \dfrac{2 + \sqrt{257}}{2}\end{array}\right.$

    Nếu đề là: $(2x -1)^2 + (x+3)^2 – 5(x – 7)(x+7) = 0$

    $\Leftrightarrow 4x^2 – 4x + 1 + x^2 + 6x + 9 – 5(x^2 – 49) = 0$

    $\Leftrightarrow 2x + 255 = 0$

    $\Leftrightarrow x = -\dfrac{255}{2}$

    Bình luận

Viết một bình luận